Analisis Deret Vokal Dalam Cerpen “Cerita Si Kancil Dan Buaya” - Suci Barkah; Ardhitya Akbhar; Jihan Suni Nurkhaerunisa N (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This study discusses the vocal series as a sequence of elements in a series of sounds. This abstract reviews the concept of vocal series from a theoretical and practical point of view, focusing on the analysis of vocal series in the short story "the story of the mouse deer and the crocodile". This study aims to investigate the properties of vocal series and their potential in providing new insights related to understanding and application of vocal series in sound processing technology. explore the use of vowel series in language and understand their role in creating nuance in stories. Qualitative analysis methods are used to explore the meaning contained in vowel series, explain the relationship between vowel use and characters, and identify linguistic patterns that enrich the narrative. The findings from this study may provide additional insight into the use of language in short stories and the contribution of vocal series to the formation of the story's atmosphere.